Pengaruh Agile Work Practice Terhadap Safety Compliance dan Emotional Fatigue Melalui Job Demand Pada Wartawan Indonesia: The Influence of Agile Work Practice on Safety Compliance and Emotional Fatigue Through Job Demand in Indonesian Journalists - Ridswan, Muhammad; Ramli, Abdul Haeba (School of Business, Bogor Agricultural University (SB-IPB), 2023)
The purpose of this study were to identifify the influence of agile work practices both directly and indirectly on job demand, emotional fatigue and safety compliance for Indonesian television journalists after two years of being hit by the co-19 pandemic in 2019-2021. In this study, the method used to analyze and determine the level of significance and interrelationships between variables is to use the Structural Equation Modeling Partial Least Squares (SEM PLS) analysis tool. The results of a study of 218 journalists spread across almost all parts of Indonesia show that agile work practices have a negative effect both directly and indirectly on job demand and emotional fatigue. Job demand has a negative effect on safety compliance. The results and implications of this study have been discussed and assessed as having an empirical influence on both theory and practice on television mass media companies in Indonesia. Keywords: agile work practices, emotional fatigue, job demands, safety compliance, structural equation modeling